BAPTISAN MENURUT INJIL YOHANES DAN DALAM TRADISI BATAK TOBA - Panjaitan, Daniel Razsekar (Diegesis : Jurnal Teologi, 2025)
This study explores the theological meaning of baptism in the Gospel of John through a dialogue with the Martutu Aek ritual within the Batak Toba community. The Batak tradition concerning water in Martutu Aek provides insights that enrich the understanding of baptism, particularly in the Johannine context, and supports the development of a contextual theology relevant to the Batak people. Employing a qualitative and interdisciplinary approach that integrates biblical theology, contextual theology, and cultural anthropology, the study analyzes key texts from John 3 and 4 and interprets the symbolism of Martutu Aek ethnographically. The aim is to uncover both the resonances and theological tensions between the two. The findings indicate that, while both emphasize purification, identity formation, and communal integration through water, the concept of “living water” in the Gospel of John offers a new theological horizon for Martutu Aek, whereas Martutu Aek enriches the understanding of baptism in relational and cultural dimensions. This dialogue contributes to the formation of an initiation theology that is more grounded, relevant, and incarnational for the Batak church.